2005
DOI: 10.1091/mbc.e04-12-1113
|View full text |Cite
|
Sign up to set email alerts
|

Role of the NH2-terminal Membrane Spanning Domain of Multidrug Resistance Protein 1/ABCC1 in Protein Processing and Trafficking

Abstract: Multidrug resistance protein (MRP)1/ABCC1 transports organic anionic conjugates and confers resistance to cytotoxic xenobiotics. In addition to two membrane spanning domains (MSDs) typical of most ATP-binding cassette (ABC) transporters, MRP1 has a third MSD (MSD0) of unknown function. Unlike some topologically similar ABCC proteins, removal of MSD0 has minimal effect on function, nor does it prevent MRP1 from trafficking to basolateral membranes in polarized cells. However, we find that independent of cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 41 publications
2
79
0
2
Order By: Relevance
“…Whereas one report proposed that the PDZ-binding motif is the apical targeting signal of ABCC2 [46], this was not confirmed by all other studies [34, 93,124,183]. These latter studies indicate that the apical targeting motif of ABCC2 is not a distinct, narrowly defined amino acid sequence, but rather appears to be composed of several motifs within different parts of ABCC2 that come together only in the intact protein.…”
Section: Localization Of Abcc2 In Polarized Cells and Tissuesmentioning
confidence: 84%
See 1 more Smart Citation
“…Whereas one report proposed that the PDZ-binding motif is the apical targeting signal of ABCC2 [46], this was not confirmed by all other studies [34, 93,124,183]. These latter studies indicate that the apical targeting motif of ABCC2 is not a distinct, narrowly defined amino acid sequence, but rather appears to be composed of several motifs within different parts of ABCC2 that come together only in the intact protein.…”
Section: Localization Of Abcc2 In Polarized Cells and Tissuesmentioning
confidence: 84%
“…However, ABCC2, together with ABCC1, ABCC3, ABCC6, and ABCC10, is unique in having an additional amino-terminal polytopic membrane-spanning domain (Fig. 2) that may be required for proper function and localization [34,39,183]. The extracellular location of the amino terminus was first predicted for rat Abcc2 by computational analysis [13] and subsequently proven experimentally [24].…”
Section: Molecular Characterization Of Abcc2mentioning
confidence: 99%
“…Recently, a detailed study investigating the influence of TMD0 on the subcellular localization of MRP1 revealed that, although TMD0 is not essential for basolateral trafficking of MRP1, deletion of the TMD0 region affects the subcellular distribution of the protein [169]. About 50% of truncated protein was found in the recycling endosomes, whereas this was only 20% in the case of the intact MRP1.…”
Section: Structure Of Mrp1 and The Role Of The Amino-terminal Regionsmentioning
confidence: 99%
“…This finding suggests that TMD0 domain is important for the retention or the recycling of MRP1 to the plasma membrane. It has also been shown that both TMD0 and the remainder of the protein contain routing signals, and TMD0 becomes essential in trafficking when the COOH-terminal region of MRP1 is mutated or truncated [169]. It is important to note that the TMD0 domains in other MRP1-related proteins, including the human MRP2 and yeast cadmium factor-1 (Ycf1), are required for correct apical targeting and for proper vacuolar localization, respectively [37,98].…”
Section: Structure Of Mrp1 and The Role Of The Amino-terminal Regionsmentioning
confidence: 99%
“…It was previously thought that TMD0 had no role in trafficking to the plasma membrane or efflux function, but this view has been revisited by several mechanistic and cell biological reports [52] . It has been shown that TMD0 is important for the processing and trafficking of human MRP1 [53] . Additionally, by mutation studies, Yang et al [54] reported that the amino terminus is required for proper MRP1 function and structure.…”
Section: Multi-drug Associated Proteinmentioning
confidence: 99%